2012
DOI: 10.1111/j.1537-2995.2012.03711.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing megakaryocyte polyploidization by targeting multiple pathways of cytokinesis

Abstract: Megakaryocyte polyploidization results from modulation of a combination of distinct cytokinesis pathways. Reagents targeting distinct cytoskeletal pathways produced additive effects in final megakaryocyte ploidy. The RRI, however, showed no additive effect but produced a high final ploidy due to overlapping inhibition of multiple cytokinesis pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 34 publications
4
28
1
1
Order By: Relevance
“…56 Aurora A could function to regulate polyploidization through its role in microtubule-organizing center localization, bipolar spindle formation, and inhibition of proteins that destabilize the microtubule network (ie, stathmin and mitotic centromere-associated kinesin). [56][57][58][59][60][61] We evaluated the effect of Pak2 deletion on megakaryocyte Aurora activation and found that Pak2 2/2 megakaryocytes had decreased Aurora phosphorylation. Actin regulatory mechanisms mediated by the Pak effector LIMK and its substrate cofilin also play a role in later steps of megakaryocyte development, and in particular in proplatelet formation.…”
Section: Discussionmentioning
confidence: 99%
“…56 Aurora A could function to regulate polyploidization through its role in microtubule-organizing center localization, bipolar spindle formation, and inhibition of proteins that destabilize the microtubule network (ie, stathmin and mitotic centromere-associated kinesin). [56][57][58][59][60][61] We evaluated the effect of Pak2 deletion on megakaryocyte Aurora activation and found that Pak2 2/2 megakaryocytes had decreased Aurora phosphorylation. Actin regulatory mechanisms mediated by the Pak effector LIMK and its substrate cofilin also play a role in later steps of megakaryocyte development, and in particular in proplatelet formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown already that exposure to Y27632 prevents normal cytokinesis and increases ploidy in different types of cells, including MKs. 23,24 Strikingly, addition of a ROCK inhibitor significantly attenuated the polyploidization defect of Fanca-deficient MKs (Figure 7A-C). A slight increase of the mean ploidy was also observed in WT cells, supporting the notion that residual RhoA-ROCK activity is present in both Fanca 2/2 and WT cells and that its pharmacological inhibition improves the polyploidization process in mouse cells.…”
Section: Mks But Increases Their Genomic Instabilitymentioning
confidence: 96%
“…These chemicals are known to inhibit cytokinesis and thus restrict MK cell expansion (Avanzi et al 2012). We found that the promoted polyploidization did not affect the platelet yield per MK in a culture of CHRF-derived MKs treated with a multi-kinase inhibitor, BMS-777607 , suggesting that the number of MKs in culture was a dominant factor in determining the amount of released platelets.…”
Section: Low Efficiency Of Megakaryopoiesismentioning
confidence: 65%
“…Mature MKs can reach 128 N in the body and release thousands of platelets per mature MK (Deutsch and Tomer 2006) whereas mature MKs derived from an in vitro culture rarely attain 64 N and produce less than a hundred platelets per cell (Mattia et al 2002). Several methods have been proposed to enhance megakaryopoiesis of HSCs, such as the addition of cytokine cocktails (Panuganti et al 2013;van den Oudenrijn et al 1999), chemical treatment (Avanzi et al 2012;Giammona et al 2006;Lannutti et al 2005) and oxidative stress (Mostafa et al 2000;Ojima et al 2013). These methods can improve the in vitro megakaryopoesis as confirmed by the increase in MK surface marker expression and the promoted polyploidization to up to 50 % of polyploid MKs after a week of culturing.…”
Section: Low Efficiency Of Megakaryopoiesismentioning
confidence: 99%
See 1 more Smart Citation